The 15-item Systemic Clinical Outcome and Routine Evaluation (SCORE-15) Scale: Portuguese Validation Studies. (20th November 2015) - Vilaça, Margarida; de Sousa, Bruno; Stratton, Peter; Relvas, Ana Paula
Abstract: This study reports on the validity of the 15-item Portuguese version of the Systemic Clinical Outcome Routine Evaluation (SCORE-15; Vilaça, Silva, & Relvas, 2014 ), a brief and comprehensive measure of family functioning. Previous studies with SCORE-15 show that this version replicates the three-factor solution found for the original English version: Family strengths, Family communication and Family difficulties. In addition to reviewing previous studies, this article analyses the discriminant, convergent and predictive validity of the Portuguese SCORE-15. To do so, the SCORE-15 was administered to family members attending systemic family or couple's therapy at the start of the first and fourth sessions and also to a group of non-clinical individuals. Overall, data are reported from 618 participants, including 136 from families attending systemic therapy and 482 community family members. Comparisons of community and clinical samples (discriminant validity) showed statistically significant differences for the total scale and subscales ( p < .001), with the community participants presenting healthier family functioning than the clinical ones. Analyses using SCORE-15 and the Quality of Life – adult version, another family measure applied simultaneously (convergent validity), indicate that both scales are significantly ( p < .01) and moderately ( r = –.47) correlated. Mean score analysis of SCORE-15's therapeutic sensitivity to change (predictive validity) showed that only the Family communication subscale was sensitive to statistically significant improvement ( p < .05) from session 1 to session 4, whereas the SCORE-15's reliability change index points to its ability to detect clinical improvements (RCI = 14%).